2023
DOI: 10.1111/vru.13242
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning predicts histologic type and grade of canine gliomas based on MRI texture analysis

Abstract: Conventional MRI features of canine gliomas subtypes and grades significantly overlap. Texture analysis (TA) quantifies image texture based on spatial arrangement of pixel intensities. Machine learning (ML) models based on MRI-TA demonstrate high accuracy in predicting brain tumor types and grades in human medicine. The aim of this retrospective, diagnostic accuracy study was to investigate the accuracy of ML-based MRI-TA in predicting canine gliomas histologic types and grades. Dogs with histopathological dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
(148 reference statements)
0
8
0
Order By: Relevance
“…After the exclusion of studies describing experimentally induced brain tum other irrelevant records, de-duplication of records appearing repeatedly in our searches using the different MeSH search phrases, and removal of studies that c < 3 cases, unconfirmed diagnoses, or limited MRI data, we identified 67 articles (F that fulfilled the inclusion criteria, with these studies reporting a total of 1630 cani 59 studies) and 125 feline cases (from 9 studies) with tumors [2,[6][7][8][9][10][11][12][13]25,26, of 62/67 studies were classified using Oxford hierarchal evidentiary criteria [2 (73%) were level 2b retrospective cohort studies [2,6-11,25,26,29,31-33,35-37,40-4 59,63-67,69-72,74,77,78,81-83], 14/62 (23%) were level 4 case series each describ animals [30,38,43,47,49,50,58,61,62,73,75,76,79,80], and 3/62 (4%) were level 3a 'm views containing source data quality heterogeneity [12][13][14]. Five radiomic stud identified [34,[44][45][46]68], with all radiomic studies having QUADAS-2 scores ≤ 6, were considered to provide low-level evidence [28]. The radiomic studies includ high risk of bias within the patient selection domain, manifesting as small sam given the number of variables tested or imbalances among analytical subgroups For the generation of a prioritized list of differential diagnoses based on characteristics of brain lesions, a recurrent theme that emerged from the literatur identify the number of lesions (solitary; multifocal/diffuse) present and then cla neuroanatomic locati...…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After the exclusion of studies describing experimentally induced brain tum other irrelevant records, de-duplication of records appearing repeatedly in our searches using the different MeSH search phrases, and removal of studies that c < 3 cases, unconfirmed diagnoses, or limited MRI data, we identified 67 articles (F that fulfilled the inclusion criteria, with these studies reporting a total of 1630 cani 59 studies) and 125 feline cases (from 9 studies) with tumors [2,[6][7][8][9][10][11][12][13]25,26, of 62/67 studies were classified using Oxford hierarchal evidentiary criteria [2 (73%) were level 2b retrospective cohort studies [2,6-11,25,26,29,31-33,35-37,40-4 59,63-67,69-72,74,77,78,81-83], 14/62 (23%) were level 4 case series each describ animals [30,38,43,47,49,50,58,61,62,73,75,76,79,80], and 3/62 (4%) were level 3a 'm views containing source data quality heterogeneity [12][13][14]. Five radiomic stud identified [34,[44][45][46]68], with all radiomic studies having QUADAS-2 scores ≤ 6, were considered to provide low-level evidence [28]. The radiomic studies includ high risk of bias within the patient selection domain, manifesting as small sam given the number of variables tested or imbalances among analytical subgroups For the generation of a prioritized list of differential diagnoses based on characteristics of brain lesions, a recurrent theme that emerged from the literatur identify the number of lesions (solitary; multifocal/diffuse) present and then cla neuroanatomic locati...…”
Section: Resultsmentioning
confidence: 99%
“…The infarct is heterogeneously iso-to hypointense on T2*GRE, is rin hancing, associated with significant mass effect, and demonstrates T2W blackout (lesion hypoi sity on DWI and ADC) due to susceptibility effects of hemorrhage. On DWI and ADC image peripheral hyperintensity surrounding the hypointense lesion core represents perilesional ede The primary neoplastic differential diagnostic considerations for solitary intramasses are neuroepithelial tumors, among which oligodendrogliomas and astrocyto (i.e., gliomas) predominate in the dog (Figure 5, Cases 16-20), with other uncommo rare possible differentials including undefined glioma (oligoastrocytoma), brain met sis, ependymoma, lymphoma, HS, and embryonal tumors [2,9,10,31,32,55,[66][67][68][69][70][71][72][73][74][75][76][77][78][79][80]. Glio can have wide-ranging MRI appearances, resulting in imaging features that may ove substantially with brain abscesses, ischemic and hemorrhagic brain infarctions, fu granulomas, immune-mediated encephalitides, leukoencephalopathies, and meningi [2,[6][7][8]10,[12][13][14]67,77,78].…”
Section: Solitary Intra-axial Mass Lesionsmentioning
confidence: 99%
See 3 more Smart Citations